Mortality Risk among Heroin Users Accessing Treatment: Natives and Non-Natives Patients Results of a Longitudinal Study. Issue 2 (14th March 2020) - Pavarin, Raimondo Maria; Sanchini, Samantha; Marani, Silvia; Turino, Elsa; Tadonio, Leonardo; Cantarelli, Barbara
ABSTRACT: The aim of this study was to examine mortality risk and causes of death for natives and non-natives in a cohort of heroin population of treated in Northern Italy. Crude Mortality Rates (CMRs) were 12.78 per 1, 000 Person Years (PY), Standardized Mortality Rate (SMR) was 9.93. Mortality has been decreasing over time, was higher for patients who accessed the treatment services before 2001 and has been increasing with age. CMRs and SMRs were higher among natives, while non-natives were distinguished by higher CMRs and SMRs for suicide. The natives were at greater risk of death than non-natives both injecting and non-injecting, but the mortality risk was not statistically significant in the different periods of first admission. Among non-native patients, older on average, there was a lower proportion of injecting, and a higher quota of people unemployed than among Italian natives. We highlight differences between the various areas of origin concerning consumption patterns and risk of death. The results of the study highlight a particular sub-population of heroin users, the non-natives, who as compared with the Italians, have less invasive consumption styles, reach the health services later but benefit from fewer medical controls.